Incidentally Discovered Appendiceal Mucinous Neoplasm in a 5-month-old Patient: A Case Report and Review of Literature - Nagpal, Ruchi; Malhotra, Purnima (Indian Journal of Medical and Paediatric Oncology, 2020)
Mucocele of the appendix is a rare entity in pediatrics, and few case reports have been reported in the literature. We present the case of a 5-month-old male with abdominal distension, constipation, and vomiting who was found to have an appendiceal mucocele while being evaluated for total colonic aganglionosis. Laparoscopic-assisted resection was performed, with pathology confirming a low-grade mucinous neoplasm of the appendix. He underwent complete resection, rendering him cured without the need for any further resection or treatment.
Keywords: Appendix; low-grade mucinous neoplasm; mucocele